تحديات قطاع التأمين الفلاحي في الجزائر: Challenges of the agricultural insurance sector in Algeria - مانع فاطمة (Journal of North African Economies, 2025)
The agricultural sector in Algeria is considered one of the most vital sectors that the state relies on to increase economic growth and raise exports outside the hydrocarbon sector, as it is the sector that achieves food security for the community. This study came to reveal the growth of the agricultural insurance sector in Algeria during the period 2010-2021, and to identify the objective problems that affect its growth, in order to propose solutions that return the agricultural insurance sector to the right direction for which it was found. The study concluded that the agricultural insurance sector records fluctuating growth from year to year, rising in one period and declining in later periods, which indicates that the sector is in dire need to change the factors controlling it, including the provision of new insurance services.